2017
DOI: 10.1002/jso.24880
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with local recurrence after surgery for bone metastasis to the extremities

Abstract: LR after surgery for bone metastasis to extremities is affected by surgical margin and primary cancer type. These factors, along with expected patient survival, need to be considered when planning surgery for bone metastasis to extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In patients with a particularly good survival prognosis such as those with solitary metastases from breast cancer or renal cell carcinoma, en bloc resection and reconstruction with a tumour prosthesis is justified as these tumours have a lower risk of relapse. En bloc resection in these cases is also associated with improved survival[ 19 , 25 ].…”
Section: Methods and Outcome Of Surgical Treatmentmentioning
confidence: 99%
“…In patients with a particularly good survival prognosis such as those with solitary metastases from breast cancer or renal cell carcinoma, en bloc resection and reconstruction with a tumour prosthesis is justified as these tumours have a lower risk of relapse. En bloc resection in these cases is also associated with improved survival[ 19 , 25 ].…”
Section: Methods and Outcome Of Surgical Treatmentmentioning
confidence: 99%
“…For these reasons, we firmly believe that it is fundamental that the survival curve of the implants should always be above the survival curve of the patients, especially in metastatic disease 32 . It is widely reported that resection and prosthetic reconstruction is associated with a lower risk of complications and more extended durability compared to other systems of fixation [32][33][34][35][36][37][38] . Steensma et al 32 reported complications after surgical treatment of 298 patients with proximal femur metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Such resections and reconstructions comprise some of the most surgically complex procedures we perform as orthopaedic oncologists. Understanding that resections without a reconstruction can result in impaired function, 33,34 there has been a demand to develop more efficient and precise reconstructive options. Throughout the field of orthopaedic surgery, the production of 3D custom implants has become increasingly popular.…”
Section: Surgical Management and Technological Developmentsmentioning
confidence: 99%